Pro-inflammatory cytokine (IL-6) and total count lymphocyte profiles in COVID-19 patients with different severity levels - Shinta Dewi Permata Sari; Wening Tri Mawanti; Dewi Martalena; Erlin Listiyaningsih; Rizkyana Avissa; Rini Latifah; Wawang S Sukarya (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
COVID-19 is caused by the SARS-CoV-2 infection that attacked the human respiratory system. In severe conditions, it causes pneumonia, kidney failure, acute respiratory distress syndrome (ARDS), and even death. The SARS-CoV-2 infection triggers the immune cells to secrete an excess of pro-inflammatory cytokines lead to cytokine storm. It is believed to become one of the mechanisms that cause the ARDS condition. The level of pro-inflammatory cytokines will differ with each case severity. This study aimed to evaluate the profile of pro-inflammatory cytokines in COVID-19 patients with different severity. Therefore, it could be used as therapeutic approach for cytokine storm conditions. It was a cross sectional study using plasma samples of COVID-19 patients from Jakarta Islamic Hospital, Pondok Kopi and Dr. M. Goenawan Partowidigdo Hospital, Cisarua, Indonesia. The COVID-19 patients with severe (n=20) and mild to moderate (n=25) severity were involved in this study. As negative control plasma sample from healthy subjects (n=13) was used. Plasma IL-6 levels were measured using the ELISA technique and plasma lymphocyte levels were measured using a hematology analyzer. The results showed that no significant difference between severity and gender was observed (p=0.256). Meanwhile, there is a significant difference in IL-6 level between negative control, mild-moderate, and severe categories (p=0.015). The average IL-6 level in severe categories was higher than mild-moderate and negative control categories, with values 105.375, 59.75, and 64.577 pg/mL, respectively. This result becomes supporting evidence that there is a cytokine storm condition in severe COVID-19 patients. Furthermore, the lymphocyte level in the severe group is significantly lower than the mild to moderate group. This result may indicate lymphocytopenia in the severe group.